Exploring Trade-offs in the Organization of Scientific Work: Collaboration and Scientific Reward - Bikard, Michaël; Murray, Fiona; Gans, Joshua S. (Management Science, 2015)
When do scientists and other innovators organize into collaborative teams, and why do they do so for some projects and not others? At the core of this important organizational choice is, we argue, a trade-off scientists make between the productive efficiency of collaboration and the credit allocation that arises after the completion of collaborative work. In this paper, we explore this trade-off by developing a model to structure our understanding of the factors shaping researcher collaborative choices, in particular the implicit allocation of credit among participants in scientific projects. We then use the annual research activity of 661 faculty scientists at the Massachusetts Institute of Technology over a 31-year period to explore the trade-off between collaboration and reward at the individual faculty level and to infer critical parameters in the collaborative organization of scientific work. This paper was accepted by Lee Fleming, entrepreneurship and innovation.